(untitled) (International Association of Biologicals and Computational Digest, 2023)
Across the world, medicinal plants have been used for thousands of years to cure and prevent a wide range of illnesses. The koli and bharvad peoples of the kotda village in dhandhuka continue to rely on medicinal plants, and the most of them have a general understanding of the plants’ uses as first aid treatments for treating common illnesses including coughs, colds, fevers, headaches, and venomous bites. There hasn’t been till now a systematic record of dhandhuka’s ethnobotany or the plants that the rural peoples use for their daily needs. A lot of work in the field of ethnobotany has been done in the north and south Gujarat, but the central part of Gujarat contains less documentation of the ethnomedicinal plants. Dhandhuka is a totally unexplored region in the field of ethnobotany. 83 plant species related to ethnobotany had been reported belonging to 47 families from dhandhuka. Most of the material that is now available is concentrated on medicinal herbs utilized by conventional healers. This study’s objective was to precisely document the existing indigenous knowledge of local people of the region of the most significant and practical flora.